Validitas Media Interaktif Scratch Menggunakan Model Problem Based Learning Pada Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Reinita, R; Hanifah, H (SAFE-Network, 2025)
This research is motivated by the transformation of Education 5.0, which fully utilizes technological advances. In line with the dynamics of the times, the curriculum structure is also constantly being updated to accommodate ongoing changes. Therefore, the implementation of the independent curriculum has been applied at present. The subject of Pancasila Education has become an integral component within the structure of the independent curriculum for the elementary education level. However, several challenges exist, including the urgency for interactive learning media, low motivation for learning, insufficient training in educational technology for educators, and limited internet connectivity access within school environments. To address these issues, effective interactive learning media are needed for education, such as Scratch, using the Problem-Based Learning model, as well as the Research and Development (R&D) method with the ADDIE Development Model. Based on the average calculations from the three validators, where the final validation results for the material were 86.6%, language validation 90%, and media validation 92%, the final validation score was 89.53% with the category of highly valid. This finding indicates that the developed learning media meets the standards of suitability and can be effectively implemented in classroom learning activities.